Andragogy Learning Strategies In The English Teaching Village Program: Survey Study at Mahesa Institute - Nahuda; Kunaenih; Muhammad, Andhika Putra; Jannah, Auliya Miftahul; Satyadinata, Bima; Taufiqurrahman, Dani; Sugarti, Rafika Mahdavikia (INTERNATIONAL JOURNAL OF ECONOMICS, MANAGEMENT, BUSINESS, AND SOCIAL SCIENCE (IJEMBIS), 2023)
This research is related to andragogy (adult) learning in the English teaching village program at the Mahesa Institute. Many adults who feel they are still lacking in education are rushing to get education, whether formal, informal or non-formal. Currently, many course institutions offer intensive learning, which gives adults the opportunity to take part in learning according to their needs. The aim of this research is to analyze andragogy learning strategies in the English Village teaching program. This research uses a descriptive-analytical method with a qualitative approach using observation and interviews. This research shows various answers from tutors regarding the strategies applied in the andragogy learning process at the Mahesa Institute. The aim of this research is to show that the strategies used are effective in learning.